2021
DOI: 10.1016/j.cub.2021.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Wild Goffin’s cockatoos flexibly manufacture and use tool sets

Abstract: Highlights d Wild Goffin's cockatoos use a tool set to access seed matter of a tropical fruit d Only few individuals engage in the behavioral sequence required for tool use d Up to three tool types are employed, differing in manufacture, size, and function d Flexible manufacture and use of tool sets is no longer restricted to primates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 56 publications
(72 reference statements)
0
31
0
Order By: Relevance
“…However, he came up with a solution for daily feather care: he collected pebbles by holding them between his tongue and lower beak and used those pebbles for preening (Bastos et al 2021a ). In a different study, individual Goffin´s cockatoos have been observed to manufacture and use sets of tools, likely as a result of individual innovative behavior rather than habitual species-wide tool use (O’Hara et al 2021 ). We will elaborate more on both aforementioned examples in the ‘physical domain – tool use’ section.…”
Section: Domain Generalmentioning
confidence: 99%
See 2 more Smart Citations
“…However, he came up with a solution for daily feather care: he collected pebbles by holding them between his tongue and lower beak and used those pebbles for preening (Bastos et al 2021a ). In a different study, individual Goffin´s cockatoos have been observed to manufacture and use sets of tools, likely as a result of individual innovative behavior rather than habitual species-wide tool use (O’Hara et al 2021 ). We will elaborate more on both aforementioned examples in the ‘physical domain – tool use’ section.…”
Section: Domain Generalmentioning
confidence: 99%
“…Furthermore, research on reasoning by exclusion with strict controls has further confirmed that this ability is present in African grey parrots (Pepperberg et al 2019 ). Finally, throughout the past 4 years, several coincidental observations of innovative behavior (outside an artificial/experimental context) were systematically recorded, leading to important insights (Klump et al 2021 ; O’Hara et al 2021 ; Bastos et al 2021a ). We are optimistic that the recent focus on parrot cognition will enable more such opportunities.…”
Section: Domain Generalmentioning
confidence: 99%
See 1 more Smart Citation
“…Such tool ‘safekeeping’ has indeed been observed anecdotally in otters ( Hall and Schaller, 1964 ), chimpanzees ( Nishida and Hiraiwa, 1982 ), and Galapagos woodpecker finches ( Tebbich et al, 2012 ), and first controlled studies have examined the behaviour’s context-dependent expression in New Caledonian crows Corvus moneduloides ( hereafter ‘NC’ crows) ( Klump et al, 2015b ) and Goffin’s cockatoos ( Auersperg et al, 2017 ). Specifically, we have previously shown experimentally that NC crows respond to an increase in tool recovery costs (foraging at height) with elevated levels of safekeeping behaviour ( Klump et al, 2015b ), a result that was subsequently replicated in Goffin’s cockatoos ( Auersperg et al, 2017 ) – a species that does not seem to routinely use tools in the wild ( O’Hara et al, 2021 ). Interestingly, when NC crows’ preferred safekeeping method of holding tools underfoot was made more challenging, because subjects had to handle demanding prey before re-using their tools, they resorted to storing tools more frequently in holes, thereby preventing their accidental loss ( Klump et al, 2015b ).…”
Section: Introductionmentioning
confidence: 98%
“…Individuals who are more prone to interact with and explore novel stimuli, and thus are more likely to engage with learning opportunities, develop adaptive skills and knowledge at a higher rate than more reluctant individuals. Skills and knowledge gained through innovation may increase an individual's survival and/or reproduction by enabling the exploitation of a novel resource or the use of a current resource more e ciently [9,13,14]. Therefore, how well individuals realize learning opportunities ultimately affects their tness.…”
Section: Introductionmentioning
confidence: 99%